2009
DOI: 10.1177/1350507608101226
|View full text |Cite
|
Sign up to set email alerts
|

Becoming (a) Practice

Abstract: This article presents findings from longitudinal ethnographic research of a mega-project alliance. For five years we followed the leadership team of a large Australian Alliance Program made up of a large public and several private organizations, analyzing `practice' as novel patterns of interaction developed into predictable arrays of activities, changing and transforming while at the same time continuing to be referred to as `the same'. In this article we focus on three such arrays of activities: authoring bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 17 publications
0
51
1
2
Order By: Relevance
“…This is different from what we might expect from the literature, where the existence of a community is generally presumed (Haythornthwaite, 2006;Lyall and Meagher, 2012). This presumption holds even when authors are clear that this community is nevertheless realized through practice; they still assume that some stable social structure is necessary for the maintenance and development of practices (see Bjørkeng et al, 2009;Gherardi, 2009b).…”
Section: Practices At the Interface Of Interacting Communitiescontrasting
confidence: 51%
See 3 more Smart Citations
“…This is different from what we might expect from the literature, where the existence of a community is generally presumed (Haythornthwaite, 2006;Lyall and Meagher, 2012). This presumption holds even when authors are clear that this community is nevertheless realized through practice; they still assume that some stable social structure is necessary for the maintenance and development of practices (see Bjørkeng et al, 2009;Gherardi, 2009b).…”
Section: Practices At the Interface Of Interacting Communitiescontrasting
confidence: 51%
“…It has also been suggested that transformations associated with new, distinct collaborative norms could be transmitted through the socialization systems of collaborative communities (Adler et al, 2008;Olsen, 2009) and that practices are involved in the generation of community (Bjørkeng et al, 2009;Gherardi, 2009aGherardi, , 2009bNicolini, 2011). But this brings us to the chicken-and-egg relationship of practice and community, since emergent collaborative practices do not 'belong' to any pre-existing stable community.…”
Section: From Practices To Communities: the Case Of Idrmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies analyse the process of the constitution and the continuous reconstitution of practices [47][48][49]. These studies are particularly interested in the formation of practices [50]. Related to sustainability some studies seek to reduce the sustainability gap by analysing sustainable strategy formation [38], yet other study citizen-consumers as agents of changes [51].…”
Section: Discussionmentioning
confidence: 99%